(untitled) (KULT_online, 2012)
Recent years have seen the publication of two edited volumes trying to bridge the gap between postcolonial studies and sociology. The English language volume Decolonizing European Sociology edited by Encarnación Gutiérrez Rodríguez, Manuela Boatcă, and Sérgio Costa has a European scope, a more systematic structure, and the more prominent authors. The German language volume Postkoloniale Soziologie edited by Julia Reuter and Paula-Irene Villa offers a broader variety in topics and reflects the specific situation of postcolonial studies in Germany. It becomes clear that the postcolonial critique of sociological approaches shows a tendency for hyperboles and faces fundamental problems, which none of the volumes manages to resolve plausibly. However, both make a valuable contribution to a postcolonial reflection of sociology as well as to a sociological enrichment of postcolonial studies.